Sitem Pembiayaan Kesehatan Yang Memenuhi Hak Azazi Manusia - Meri Ulfa; Marice Simarmata (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study analyzes the health financing system in Indonesia from a human rights perspective, particularly after the enactment of Law No. 17 of 2023 concerning Health and Minister of Health Regulation No. 18 of 2022 concerning the Implementation of One Data in the Health Sector. These two regulations reflect the state's commitment to strengthening the national health system based on the principles of justice, transparency, and the fulfillment of citizens' constitutional rights to quality, equitable, and sustainable health services. Through a qualitative approach using document analysis of relevant regulations, policies, and academic literature, this study identifies a paradigmatic transformation in health financing, from merely a fiscal mechanism to a strategic instrument for guaranteeing human rights in the health sector. The results show that despite normative and institutional progress, the implementation of the health financing system still faces several challenges. These challenges include aspects of the community's economic accessibility to health services, limitations in transparency and accountability in fund management, and inequality in the distribution of financial resources between regions. In addition, funding sustainability and dependence on certain funding sources are also issues that need to be addressed. In response to these challenges, this study recommends three main strategies: (1) strengthening the integration and interoperability of financing data through the One Health Data system, (2) diversifying funding sources by involving the private sector, philanthropy, and other innovative schemes, and (3) reorienting health budget allocations to favor vulnerable groups and underdeveloped regions. These efforts are expected to encourage the realization of a fair, transparent, and sustainable health financing system within the framework of fulfilling human rights in Indonesia.